2019
DOI: 10.1111/iej.13134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of apical extent of root canal filling on vertical root fracture: a case–control study

Abstract: Aim To investigate the impact of apical extent of root filling on vertical root fracture (VRF) in a case–control study. Methodology Eighty‐six patients (119 roots) diagnosed with VRF in crowned root filled anterior and posterior teeth were selected. The cases were matched individually with control teeth in a ratio of 1:1 for age (±5 years), gender, tooth type, canal instrumentation method, master apical file (MAF) size and taper, technique of canal filling and time period after root filling. All root canals ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…From PradeepKumar et al (2019)—‘Cases were individually matched with controls in a ratio of 1:1 for age (±5 years), gender, tooth type, instrumentation system, master apical file (MAF) size and taper, technique of canal filling and time period from canal filling (similar or more for controls). Cases and controls were selected from a pool of patients treated by three qualified endodontists with more than 10 years of experience.…”
Section: Process Involved In Developing the Preferred Reporting Items...mentioning
confidence: 99%
“…From PradeepKumar et al (2019)—‘Cases were individually matched with controls in a ratio of 1:1 for age (±5 years), gender, tooth type, instrumentation system, master apical file (MAF) size and taper, technique of canal filling and time period from canal filling (similar or more for controls). Cases and controls were selected from a pool of patients treated by three qualified endodontists with more than 10 years of experience.…”
Section: Process Involved In Developing the Preferred Reporting Items...mentioning
confidence: 99%
“…15,37,38 Pitts et al, (1983) reported that a spreader load of 7.2 kg resulted in a vertical root fracture of a maxillary incisor, with 16% of the teeth tested fracturing at loads less than 10 kg. 39 However, the mean load required to induce fracture ranges from 10-20 kg. 37,38,39 A study compared the effects of lateral compaction with the continuous wave technique.…”
Section: Obturation Techniquementioning
confidence: 99%
“…39 However, the mean load required to induce fracture ranges from 10-20 kg. 37,38,39 A study compared the effects of lateral compaction with the continuous wave technique. Their results showed that root canal preparation and obturation had significantly more defects as compared to unprepared teeth.…”
Section: Obturation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The loss of the protective effect of the pulp tissue during chewing adds to the microstructural changes in the dentin that promote instrumentation; the chemical conditioning ( 8 ) and excessive forces during filling ( 9 ) are plausible factors that contribute to the failure of the dental structure, especially over time. Therefore, if 66% of VRFs were diagnosed between 2 to 5 years from the completion of root canal treatment ( 9 ), the structural changes that the treated root dentin undergoes are considered time-dependent, and the multifactorial nature of the vertical fracture does not allow the identification of a single risk factor ( 4 ). Thus, tooth structural loss, viscoelasticity loss, age-induced changes in the dentin, and restorative procedures are primary factors that usually predispose the teeth to immediate fracture.…”
Section: Introductionmentioning
confidence: 99%